Photoelectron Diffraction Imaging of a Molecular Breakup Using an X-Ray Free-Electron Laser - Kastirke, Gregor; Schöffler, Markus S.; Weller, Miriam; Rist, Jonas; Boll, Rebecca; Anders, Nils; Baumann, Thomas M.; Eckart, Sebastian; Erk, Benjamin; De Fanis, Alberto; Fehre, Kilian; Gatton, Averell; et al. (My University, 2020)
A central motivation for the development of x-ray free-electron lasers has been the prospect of time-resolved single-molecule imaging with atomic resolution. Here, we show that x-ray photoelectron diffraction—where a photoelectron emitted after x-ray absorption illuminates the molecular structure from within—can be used to image the increase of the internuclear distance during the x-ray-induced fragmentation of an O2 molecule. By measuring the molecular-frame photoelectron emission patterns for a two-photon sequential K-shell ionization in coincidence with the fragment ions, and by sorting the data as a function of the measured kinetic energy release, we can resolve the elongation of the molecular bond by approximately 1.2 a.u. within the duration of the x-ray pulse. The experiment paves the road toward time-resolved pump-probe photoelectron diffraction imaging at high-repetition-rate x-ray free-electron lasers.